SURFACE HARDENING CHARACTERIZATION OF TRANSMISSION GEARS - Rifky Ismail; . Jamari; M. Tauviqirrahman; . Sugiyanto; Trias Andromeda (Prosiding SNST Fakultas Teknik, 2011)
This paper is presented to compare the transmission gear products from SME (UKM gear) and national scale manufacturer (OEM gear) especially on the surface hardening characterization. Both gears  were  heat  treated with  different methods.  The gear product of SME was  heat treated by pack carburizing and quenching whereas the OEM gear was predicted to be heat treated using induction  heating with high frequency. The surface hardening characterization was conducted by investigating the hardening thickness,  the hardness number  and the microstructure  observation  on the gear surfaces.  The result  of the hardening thickness investigation reveals a distinction on the depth of hardening penetration. The heat treatment using  long interval  pack carburizing  of UKM gear  produces a  deeper  penetration and the higher hardness number on the gear surface whereas the OEM gear has a thin hardness penetration and lower hardness number.  The microstructure of  the  both gears  depicts the different types  of phase. The  SME  gear shows the present of the carbon  infiltration  on the martensitic phase structure boundary whereas the OEM gear exhibits lower bainite phase on the gear surface. With this condition the OEM gear is predicted to behave a better contact stress distribution during operation. Keywords: gear, heat treatment, surface hardening, microstructure